2016
DOI: 10.13065/jksdh.2016.16.05.733
|View full text |Cite
|
Sign up to set email alerts
|

Communication ability according to self-awareness and other-awareness in some dental hygiene students

Abstract: Objectives:The purpose of this study was to investigate the relationship among the factors of communication ability according to self-awareness and other-awareness in some dental hygiene students. Methods: A self-reported questionnaire was completed by 260 dental hygiene students in Gwangju and Jeonnam from June 14 to 28, 2016. After explanation of the purpose of the study, an informed consent was written by the students. The effect size was calculated by G*power 3.1 program. The study instruments comprised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The mean for communication competency was 3.46. The research in dental hygiene students 13 found it was 3.31 and the one using a different instrument in dental hygienists 10 이진 found it was 3.42. The research in nursing students 20 got a higher score (3.73) than this study and Lim 13 noted that nursing students' greater communication competency was related to communication education.…”
Section: 7discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean for communication competency was 3.46. The research in dental hygiene students 13 found it was 3.31 and the one using a different instrument in dental hygienists 10 이진 found it was 3.42. The research in nursing students 20 got a higher score (3.73) than this study and Lim 13 noted that nursing students' greater communication competency was related to communication education.…”
Section: 7discussionmentioning
confidence: 98%
“…The research in dental hygiene students 13 found it was 3.31 and the one using a different instrument in dental hygienists 10 이진 found it was 3.42. The research in nursing students 20 got a higher score (3.73) than this study and Lim 13 noted that nursing students' greater communication competency was related to communication education. The Korean Accreditation Board of Nursing Education suggests communication competency as key capability that a nurse is required to be equipped with and communication education is considered very important in nursing curriculums 18 .…”
Section: 7discussionmentioning
confidence: 98%
“…Dental hygiene students are experiencing many conflicts and difficulties during clinical practice due to insufficient communication ability and interpersonal skills. It is reported that this decreases satisfaction with clinical practice and leads to skepticism about the career path 4,5) . Eventually, it has a negative effect on the adaptation of college life, which leads to dropouts such as leave of absence or withdrawal 6) .…”
Section: Introductionmentioning
confidence: 99%